Symmetric Spastic Quadriparesis with Occult Cerebral Demyelination: An Adult-Onset Adrenoleukodystrophy Case Report - Sharmila, Shaik; Jinka, Deepika; Madineni, Gnaneswari; Matta, Sruthi; Bolisetty, Guru Lakshmi; Mothadi, Bala Naga Phanindra; Nalabothu, Avinash; Mandarapu, Bhargavi Devi; Yanamadala, Pavan Kumar; Nadendla, Rama Rao (Asian Journal of Biological and Life Sciences, 2026)
X-linked adrenoleukodystrophy is a peroxisomal disorder caused by ABCD1 mutations leading to the accumulation of very-long-chain fatty acids and progressive neurological dysfunction. Adult-onset cerebral adrenoleukodystrophy is uncommon and often presents with subtle or atypical symptoms, contributing to diagnostic delays. We describe an adult male who presented with a 2-year history of gradually progressive symmetrical spastic quadriparesis, gait disturbance, and mild bulbar symptoms without cognitive decline or adrenal insufficiency. Neurological examination revealed marked spasticity, exaggerated reflexes, and frontal release signs, with preserved sensory modalities. Early magnetic resonance imaging brain demonstrated subtle, symmetrical T2/FLAIR hyperintensities in the posterior periventricular white matter, initially non-specific and non-enhancing. Routine laboratory studies were unremarkable. Further evaluation with biochemical assays showed elevated very- long-chain fatty acids, and genetic testing confirmed a pathogenic ABCD1 variant, establishing the diagnosis of adult-onset cerebral adrenoleukodystrophy. Supportive management, including spasticity control, physiotherapy, and counselling, led to functional improvement during hospitalization. This case highlights the diagnostic challenges of adult-onset adrenoleukodystrophy, particularly when cerebral demyelination is mild, and symptoms mimic hereditary spastic paraplegia, multiple sclerosis, or degenerative myelopathies. The absence of adrenal involvement and lack of florid radiological findings further contributed to delays in recognition. Clinicians should consider adrenoleukodystrophy in adults presenting with unexplained upper motor neurone syndromes, even when magnetic resonance imaging abnormalities are subtle. Early metabolic and genetic testing is essential to avoid missed therapeutic opportunities and ensure timely multidisciplinary care.
Keywords: Adrenoleukodystrophy; ABCD1 mutation; Adult-Onset Adrenoleukodystrophy (ALD); Spastic Quadriparesis; Cerebral Demyelination; Leucodystrophy; Very-Long-Chain Fatty Acids; (VLCFA)